Workers oral health: a cross-sectional study - Marília Jesus Batista; Lílian Berta Rihs; Maria da Luz Rosário de Sousa (Universidade Estadual de Campinas, 2015)
Adults and elderly usually present an expressive tooth loss in household epidemiologic studies. Few studies were found to report oral health conditions in economically active adults. Aim: To describe the oral health status of adult workers in an extended range age (20-64 years old) of a supermarket chain. Methods: This cross-sectional survey was conducted in a company in the state of São Paulo. A total of 386 workers aged 20 to 64 years old were examined following the guidelines recommended by the World Health Organization (1997) with respect to caries, treatment needs for caries, and need and use of dental prostheses. Age was stratified into groups for analysis. A descriptive analysis was performed and tooth loss rate was calculated. Kruskal Walis and Tukey's tests were used for the evaluation of differences in DMTF and chi-square test was used for treatment needs. Results: The mean DMFT was 14.6 (± 8.3), and differences were found among the 3 groups, mainly due to missing teeth. DMFT was 10.8 (±6.95) in the 20-34- year-old group, 19.6 (±6.13) in the 35-44-year-old group and 22.1(±7.32) in the 45-64-yearold group. Significant differences in tooth loss rate were observed between the age groups (tooth loss rate ranged from 18% to 81%). Among the adults, 53.5% had treatment needs for caries. Conclusions: The younger adult workers in this study showed better oral conditions and an increase in tooth loss was observed in the older individuals. Considering common risk approach, dentistry should work together with health promotion for the studied population of workers in order to meet the oral treatment needs and prevent new tooth losses.